Comparison of hexavalent chromium and welding fumes inside and outside of the welding helmet - Diaz-Rivera, Karen, author; Brazile, William, advisor; Reynolds, Stephen, committee member; Collett, Jeffrey L., committee member (Colorado State University. Libraries, 2013)
The primary objective of this study was to determine if welding fumes and specific metal concentrations were significantly different between samples taken inside and outside of the welding helmet to determine the most appropriate location of the personal sampling device and best estimate exposure. Personal air samples were collected simultaneously inside and outside of the welding helmet for concentration comparison of welding fumes (n = 12) and hexavalent chromium (n = 15) during stainless steel tungsten inert gas welding tasks. A total of fifteen welders were sampled in a manufacturing setting and a brewery for a total of 27 inside and outside paired samples. A statistically significance difference (p = 0.05) between inside and outside welding helmet concentrations was found for total welding fumes, iron, total chromium, and nickel using a Wilcoxon paired test, where most of the inside-helmet concentrations were lower. Hexavalent chromium and manganese concentrations were not significantly different when comparing inside and outside welding helmet concentrations. A correlation among welding fumes, iron, nickel, and total chromium concentrations was observed utilizing Spearman's rank-order correlation. The mean for hexavalent chromium concentrations difference was 11 μg/m3, when the outlier was included in the analysis and 0.07 μg/m3 without the outlier. The median concentrations difference was 0.06 μg/m3 with or without the outlier in the analysis. The 95% confidence interval for hexavalent chromium inside concentration was 0.1 μg/m3 to 0.34 μg/m3 and 0.13 μg/m3 to 0.4 μg/m3 for outside of the welding helmet concentration. One sample set for hexavalent chromium exceeded the permissible exposure limit (PEL), recommended exposure limit (REL), and threshold limit value (TLV). Based on the results, a high variation of concentrations was found between the inside and outside of the welding helmet concentrations depending on the metal fume analyzed. Manganese had the lowest metal content in the stainless steel welding rods as well as the sampled welding fumes. The greatest variation in concentration ratios was observed for manganese and hexavalent chromium when comparing inside and outside concentrations. These two factors, lower metal contribution in welding rods and variation in concentrations can be speculated to affect the statistical non significant difference found for manganese and hexavalent chromium inside and outside of the welding helmet concentrations. The welding helmet seemed to be protective for some metals, but it should not be assumed that protection will be provided by the use of it. As for sampling location for best welding fumes assessment monitoring, it is recommended that sampling is done outside. Welders often remove their welding helmets to verify the weld, and inside of the welding helmet sampling location may be compromised as it may change when the welding helmet is in the upward position.
Keywords: welding fumes; hexavalent chromium; welding helmet